Characterizing leaf-deposited particles: Single-particle mass spectral analysis and comparison with naturally fallen particles - Dele Chen; Hua-Yun Xiao; Ningxiao Sun; Jingli Yan; Shan Yin (Environmental Science and Ecotechnology)
The size and composition of particulate matter (PM) are pivotal in determining its adverse health effects. It is important to understand PM's retention by plants to facilitate its atmospheric removal. However, the distinctions between the size and composition of naturally fallen PM (NFPM) and leaf-deposited PM (LDPM) are not well-documented. Here we utilize a single-particle aerosol mass spectrometer, coupled with a PM resuspension chamber, to analyze these differences. We find that LDPM particles are 6.8–97.3% larger than NFPM. Employing a neural network algorithm based on adaptive resonance theory, we have identified distinct compositional profiles: NFPM predominantly consists of organic carbon (OC; 31.2%) and potassium-rich components (19.1%), whereas LDPM are largely composed of crustal species (53.9–60.6%). Interestingly, coniferous species retain higher OC content (11.5–13.7%) compared to broad-leaved species (0.5–1.2%), while the levoglucosan content exhibit an opposite trend. Our study highlights the active role of tree leaves in modifying PM composition beyond mere passive capture, advocating for a strategic approach to species selection in urban greening initiatives to enhance PM mitigation. These insights provide guidance for urban planners and environmentalists in implementing nature-based solutions to improve urban air quality.